2022-RA-1595-ESGO The role of sentinel lymph node biopsy in the management of patients with endometrial atypical hyperplasia: a multicenter study. (20th October 2022) - Rosati, Andrea; Vargiu, Virginia; Capozzi, Vito Andrea; Palmieri, Emilia; Baroni, Alessandro; Perrone, Emanuele; Cosentino, Francesco; Berretta, Roberto; Scambia, Giovanni; Fanfani, Francesco
Abstract : Introduction/Background: The role of sentinel lymph node mapping in patients with complex atypical hyperplasia (CAH) is a debated topic in literature and needs to be clarified.The aim of this study was to describe the surgical outcomes, intra-postoperative complications of patients with CAH undergoing a radical surgical staging with or without sentinel-lymph-node (SLN) biopsy, and to describe the incidence and histopathological features of endometrial cancer (EC) diagnosed in each group. Methodology: All patients with pre-operative diagnosis of CAH were retrospectively retrieved. Study population was subdivided based on surgical staging procedures in Group-1 (total hysterectomy) and Group-2 (total hysterectomy plus SLN-biopsy). Results: 460 patients were identified (Group-1:192, Group-2: 268).The surgical approach differed significantly between the two groups, with a higher rate of robotic procedures in Group 2 and laparoscopic procedures in Group 1 (28.7% vs 6.3% and 75.5% vs 63.1%, respectively, p <0.001).No disparities in surgical variables were registered between Group-1 and 2 regarding estimated blood loss and operative time (respectively: p=0.075, p=0.143).Furthermore, both severe and overall rate of intraoperative (IO) and postoperative complications did not significantly vary across Groups (respectively: no severe IO complications occurred, p=0.868, p=0.489, p=0.07).At final histopathological examination the incidence of EC was significantly higher in Group 2 (p<0.001).Considering only EC cases, the distribution of prognostic risk groups did not significantly vary within Groups (p=0.329), while in the overall series the most frequent risk class was Low (71.4%), followed by High-intermediate (11.1%), Intermediate (9.7%) and High (7.8%).The rate of understaging was 28.1% and the rate of overtreatment 39.2%. Conclusion: SLN dissection is a safe and not time-consuming procedure that can be proposed while counseling patients for radical treatment of CAH.During the decision-making process the 28.1% rate of understaging together with a non-negligible proportion of High-intermediate and High-risk classes should be balanced with a 39.2% ratio of overtreatment.